ポーランド ホッキョク カンソク キチ ホーンスン ノ ショウカイ - 伊藤, 一; イトウ, ハジメ; Ito, Hajime (2005)
P(論文) ポーランドは,スバールバル諸島スピッツベルゲン島のホーンスン・フィヨルドに北極観測基地を設け,通年観測を行っている.この観測基地は,非北極国が独自に運営する通年北極観測基地としては,世界中で唯一のものである.このたび,同基地について調査する機会を得たので,報告する. Poland operates a year-round Arctic station at Hornsund, Spitsbergen, Svalbard. It is the only permanent Arctic station which a non-Arctic state operates independently. The author was given an opportunity to visit the station, and a brief report is prepared. departmental bulletin paper